Ethical issues in social work - Hugman, Richard, 1954-; Smith, David, 1947 August 2- (Professional ethics., 1995)
It has always been recognised that the practice of social work raises ethical questions. This collection of essays explores these questions in the light of recent developments in philosophy and in social work theory and practice.